2012
DOI: 10.1111/j.1440-1746.2011.06889.x
|View full text |Cite
|
Sign up to set email alerts
|

Is transient elastography valuable for high‐risk esophageal varices prediction in patients with hepatitis‐B‐related cirrhosis?

Abstract: TE may predict HREV in patients with ALT ≥ 5 × ULN. Overall, the clinical values of TE and USLS for HREV prediction should be evaluated by further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
(89 reference statements)
0
14
0
1
Order By: Relevance
“…Ten studies did not provide sufficient information to be able to ascertain if the investigators that performed the endoscopy were unaware of the LS value, or vice versa, which put them at risk of review bias (8,9, 14,15,18,21,23,24,29,30). The time interval between the performance of EGD and the performance of the TE was too long in 2 studies (28,30) and undefined in 8 studies (8,14,15,(20)(21)(22)24,25), putting them at risk of disease progression bias.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies did not provide sufficient information to be able to ascertain if the investigators that performed the endoscopy were unaware of the LS value, or vice versa, which put them at risk of review bias (8,9, 14,15,18,21,23,24,29,30). The time interval between the performance of EGD and the performance of the TE was too long in 2 studies (28,30) and undefined in 8 studies (8,14,15,(20)(21)(22)24,25), putting them at risk of disease progression bias.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the flow diagram of literature search and study selection. (15,16,19,20,22,24,27). The other 3 studies were performed in Africa (Egypt [17,29] and Morocco [25]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Established evidences have indicated that LSM has good sensitivity and specificity for liver fibrosis and cirrhosis. So, it has become popular over the past few years especially for obtaining repeated measurements because it eliminates pain, morbidity and mortality that may accompany liver biopsy 2527…”
Section: Introductionmentioning
confidence: 99%
“…Transient elastography (TE) is a non‐invasive tool that measures liver stiffness (LS) correlating to liver fibrosis stage. While TE also shows potential in the prediction of EV, its role is still under debate. Moreover, the LS‐spleen size‐to‐platelet ratio score (LSPS), which is a combination of three simple examination methods (LS, spleen size and platelet count) has been established to accurately predict EV in patients with compensated cirrhosis .…”
Section: Introductionmentioning
confidence: 99%